Endoplasmic reticulum stress and associated apoptosis are linked with the pathogenesis of white striping in broiler breast muscles - İpek, Emrah; Ahsan, Umair; Özsoy, Bülent; Ekren Aşıcı, Gamze Sevri; Tatar, Musa; Özpilavcı, Beyza Nur; Epikmen, Erkmen Tuğrul; Özsoy, Şule Yurdagül; Khamseh, Ehsan Karimiyan; Petracci, Massimiliano (Elsevier BV, 2024)
White striping (WS) that appears as white stripes parallel to the muscle fibrils is an emerging growth-related abnormality of broiler breast meat. The pathomechanism of this defect has not been fully understood despite intensive studies over the past decade. In the present study, endoplasmic reticulum (ER) stress and its associated apoptotic pathways were investigated to elucidate the potential role of these pathways in the development of WS. To this end, a total of 60 Pectoralis major (Pm) muscle samples were collected from 55-d-old Ross 308 male broiler chickens according to the severity of gross WS lesions (normal, mild, and severe). Histopathological and molecular analyses were conducted to evaluate the lesions and genes involved in the ER stress and related apoptosis. All the Pm samples, both with and without macroscopic WS lesions, showed varying degrees of myodegenerative lesions. Molecular analysis revealed that the transcript abundances of many components related to protein kinase R-like ER kinase (PERK) and inositol-requiring enzyme type 1 (IRE-1) signals of the ER stress response were significantly greater in severely WS-affected breast tissues compared to their mildly affected and normal counterparts. Similarly, the transcript abundances of apoptotic markers related to both signaling pathways were significantly greater in severe WS lesions than those of mildly affected and normal Pm tissues. Besides these, a significant increase in caspase-3 transcript abundance was seen in severe WS lesions in comparison with mild WS and normal breast muscles. Findings of this study suggest that ER stress response and its related apoptotic pathways are possibly activated in the breast muscle of broiler chickens with severe WS lesions. Based on these findings, it is speculated that ER stress-mediated apoptosis occupies a central role in the progression of WS in broiler chickens.
Keywords: Male; white striping; apoptosis; Apoptosis; apoptosis; broiler chicken; endoplasmic reticulum stress; white striping; Endoplasmic Reticulum Stress; SF1-1100; Animal culture; Pectoralis Muscles; Avian Proteins; broiler chicken; Muscular Diseases; IMMUNOLOGY, HEALTH AND DISEASE; endoplasmic reticulum stress; Animals; Chickens; Poultry Diseases